2022
DOI: 10.3389/fimmu.2022.1000996
|View full text |Cite
|
Sign up to set email alerts
|

The cytokine network in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is a highly heterogeneous malignancy of the blood and bone marrow, characterized by clonal expansion of myeloid stem and progenitor cells and rapid disease progression. Chemotherapy has been the first-line treatment for AML for more than 30 years. Application of recent high-throughput next-generation sequencing technologies has revealed significant molecular heterogeneity to AML, which in turn has motivated efforts to develop new, targeted therapies. However, due to the high comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 185 publications
0
13
0
1
Order By: Relevance
“…Argentine Stop Trial (AST), to date, is the largest clinical trial in Latin America of chronic phase (CP)-CML patients who stopped across all types of tyrosine kinase inhibitors (TKIs) (Additional file 1 : Supp Materials and Methods). Cytokine profiling has been suggested to be valuable in identifying predictive markers in other myeloid malignancies [ 1 ]; here, we measured plasma cytokine levels in 46 patients discontinuing TKIs with the aim of identifying predictive plasma biomarkers for TFR. Patients baseline characteristics and treatment information are shown in Additional file 2 : Table S1.…”
mentioning
confidence: 99%
“…Argentine Stop Trial (AST), to date, is the largest clinical trial in Latin America of chronic phase (CP)-CML patients who stopped across all types of tyrosine kinase inhibitors (TKIs) (Additional file 1 : Supp Materials and Methods). Cytokine profiling has been suggested to be valuable in identifying predictive markers in other myeloid malignancies [ 1 ]; here, we measured plasma cytokine levels in 46 patients discontinuing TKIs with the aim of identifying predictive plasma biomarkers for TFR. Patients baseline characteristics and treatment information are shown in Additional file 2 : Table S1.…”
mentioning
confidence: 99%
“…In acute myeloid leukaemia (AML), it is well known that abnormal secretion of pro‐inflammatory cytokines remodels the bone marrow microenvironment (BMM) in favour of AML blast survival, AML progression, and treatment resistance (Kupsa et al., 2012 ; Luciano et al., 2022 ). However, few recent studies have demonstrated that small extracellular vesicles (sEVs) released by AML cells transform the BMM into a leukaemia‐permissive microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the immune-modulatory properties of AML-MSCs, demonstrated by their ability to induce regulatory T cells, suggest their involvement in shaping the immunosuppressive microenvironment supporting leukemic cells [ 68 ]. The interaction between AML blasts and MSCs results in the release of cytokines and chemokines, contributing to the formation of a leukemic niche [ 69 ].…”
Section: Mscs In Amlmentioning
confidence: 99%